Antibodies to Neospora caninum and Toxoplasma gondii in domestic cats from Brazil - Bresciani, Katia Denise Saraiva [UNESP]; Gennari, S. M.; Serrano, A. C. M.; Rodrigues, A. A. R.; Ueno, T.; Franco, L. G.; Perri, S. H. V.; Amarante, A. F. T. (Springer, 2007)
The occurrence of antibodies to Neospora caninum and Toxoplasmagondii was determined in 400 domestic cats (Siamese, Persian, and undetermined breeds) from the Municipality of Aracatuba, São Paulo, Brazil, through the indirect fluorescence antibody test (IFAT). of the 400 cats, 100 were seropositive to T. gondii (25%, titer >= 64) and 98 to N. caninum (24.5%, titer >= 16). The rate of seropositive cats for T. gondii was correlated with age (chi(2)=35.7; p < 0.001), with a higher number of infected animals at older ages. of the 219 cats younger than 1-year-old, 13.2% were seropositive for T. gondii, while 39.2% were positive in the 181 older animals. The presence of N. caninum was also correlated with age (divided by(2)=8.8; p < 0.01), with 18.7% (41/219) and 31.5% (57/181) of positive animals at ages below and above 12-month, respectively. An association between the occurrences of both protozoa in the felines was also observed (chi(2)=19.6; p < 0.001).